Genetic Mapping and Identification of the Candidate Genes for Mottled Rind in Cucumis melo L. - Shen, Jia; Xu, Xinyang; Zhang, Yuejian; Niu, Xiaowei; Shou, Weisong (Frontiers in Plant Science, 2021)
The rind appearance of melon is one of the most vital commercial quality traits, determining consumers’ preferences and behavior towards melon consumption. In this study, we constructed an F2 population derived from SC (mottled rind) and MG (non-mottled rind) lines for mapping the mottled rind gene(s) in melon. Genetic analysis showed that there were two dominant genes (CmMt1 and CmMt2) with evidence of epistasis controlling the mottled rind. Meanwhile, the phenotypic segregation ratio implied that the immature rind color had an epistatic effect on the mottled rind, which was regulated by CmAPRR2. A KASP DNA marker (CmAPRR2SNP(G/T)) was developed and shown to co-segregate with rind color, confirming that CmAPRR2 was CmMt1. Using BSA seq and KASP assays, CmMt2 was fine-mapped to an interval of 40.6 kb with 6 predicted genes. Functional annotation, expression analysis, and sequence variation analyses confirmed that AtCPSFL1 homolog, MELO3C026282 was the most likely candidate gene for CmMt2. Moreover, pigment content measurement and transmission electron microscopy analysis demonstrated that CmMt2 might participate in the development of chloroplast, which in turn decreases the accumulation of chlorophyll. These results provide insight into the molecular mechanism underlying rind appearance and reveal valuable information for marker-assisted selection breeding in melon.